Drosophila CK1-?, gilgamesh, controls PCP-mediated morphogenesis through regulation of vesicle trafficking. - Gault, W.J.; Olguin, P.; Weber, U.; Mlodzik, M. (Journal of Cell Biology, 2012)
Cellular morphogenesis, including polarized outgrowth, promotes tissue shape and function. Polarized vesicle trafficking has emerged as a fundamental mechanism by which protein and membrane can be targeted to discrete subcellular domains to promote localized protrusions. Frizzled (Fz)/planar cell polarity (PCP) signaling orchestrates cytoskeletal polarization and drives morphogenetic changes in such contexts as the vertebrate body axis and external Drosophila melanogaster tissues. Although regulation of Fz/PCP signaling via vesicle trafficking has been identified, the interplay between the vesicle trafficking machinery and downstream terminal PCP-directed processes is less established. In this paper, we show that Drosophila CK1-?/gilgamesh (gish) regulates the PCP-associated process of trichome formation through effects on Rab11-mediated vesicle recycling. Although the core Fz/PCP proteins dictate prehair formation broadly, CK1-?/gish restricts nucleation to a single site. Moreover, CK1-?/gish works in parallel with the Fz/PCP effector multiple wing hairs, which restricts prehair formation along the perpendicular axis to Gish. Our findings suggest that polarized Rab11-mediated vesicle trafficking regulated by CK1-? is required for PCP-directed processes.